Oneness and the displacement of self : dialogues on self-realization - Krausz, Michael, 1942- (Value inquiry book series. Interpretation and translation ;, 2013)
This book presents a fictional dialogue among four former college friends about Oneness and self-realization. News of the sudden death of a relative occasions their discussion. One friend, a devotee of the Advaita or non-duality school of Hindu philosophy, seeks to short-circuit the pain and suffering characteristically associated with anxieties about human mortality. According to her, to be is to be the ultimate ineffable undifferentiated Being, the birthless and the deathless-the One. The other friends, whose philosophical attitudes are broadly pragmatist, relativist, and realist, inquire in.